A remarkable new Nilotonia species (Acari, Hydrachnidia, Anisitsiellidae) from percolating water of a cave in Cat Ba island in Halong Bay, Vietnam - Pešić, Vladimir (Zootaxa, 2013)
Both sexes of Nilotonia sketi sp. nov. are described from percolating water of a cave in Cat Ba island in Halong Bay, Vietnam. The IV-L-6 of the new species is characterized by a line of longer ventral setae, and presence of two longer distoventral setae. The systematic position of Nilotonia species attributed to the subgenera Dartiella K. Viets, 1929 and Dartonia K. Viets, 1929 are discussed. The latter subgenus is re-defined and Dartiella is proposed as its junior synonym. Two new subgenera, Gereckonia (type species: Nilotonia turcica Özkan & Soysal, 1989 from Turkey) and Davetonia (type species: Nilotonia perplexa Cook, 1967 from India) are erected.